Canine Distemper Virus in Mexico: A Risk Factor for Wildlife - Juan Macías-González; Rebeca Granado-Gil; Lizbeth Mendoza-González; Cesar Pedroza-Roldán; Rogelio Alonso-Morales; Mauricio Realpe-Quintero (Viruses)
Canine distemper is caused by a morbillivirus similar to others that affect livestock and humans. The increase in host range and its persistence in wildlife reservoirs complicate eradication considerably. Canine distemper virus has been reported in wildlife in Mexico since 2007. Dogs were previously considered the main reservoirs, but high vaccination coverage in the USA has helped control the disease, and racoons (Procyon lotor) are now recognized as the main reservoirs of the agent in the USA, since they live in high densities in urban environments (peridomestic), where contact with domestic and wildlife species is common. Racoons are now considered to spread CDV in wildlife species and zoo animals. Mexico is home to at least two wildlife species that have been reported as carriers of the CDV infection in studies in the USA. Raccoons and Coyotes are distributed in several Mexican states and could play the same reservoir role as for the US. In addition, the increase in non-traditional pets expands the availability of susceptible individuals to preserve CDV in domiciliary and peri-domiciliary environments, contributing to the spread of the disease. Combined with incomplete vaccination coverage in domestic canids, this could contribute to maintaining subclinical infections. Infected pets with incomplete vaccination schedules could also spread CDV to other canines or wildlife coexisting species. In controlled habitats, such as flora and fauna sanctuaries, protected habitats, zoo collections, etc., populations of wildlife species and stray dogs facilitate the spread of CDV infection, causing the spilling over of this infectious agent. Restricting domestic pets from wildlife habitats reduces the chance of spreading the infection. Regular epidemiological surveillance and specific wildlife conservation practices can contribute to managing threatened species susceptible to diseases like CDV. This may also facilitate timely interventions in companion animals which eventually minimize the impact of this disease in both scenarios. Aim: The review discusses the circulation of CDV in wildlife populations, and highlights the need for epidemiological surveillance in wildlife, particularly in endangered wildlife species from Mexico. Through an extensive review of recent scientific literature about CDV disease in wildlife that has been published in local and international databases, the findings were connected with the current needs of information from a local to global perspective, and conclusions were made to broaden the context of Mexican epidemiological scenarios as closely related to the neighboring regions.